Halal Bihalal Perspektif Islam dan Jawa: Pengertian Halal Bihalal, Dalil-Dalil Tentang Halal Bihalal, Halal Bihalal Perspektif Islam dan Jawa, Hikmah Halal Bihalal, Hukum Halal Bihalal - Dhiyaul Haq, Alfiyyah (Sanaamul Quran: Jurnal Wawasan Keislaman, 2024)
Abstract Halal bihalal is a unique Indonesian tradition held after the month of Ramadan, serving as a moment for mutual forgiveness and strengthening bonds between individuals and community groups. The term "halal bihalal" comes from Arabic and has assimilated with Javanese culture. In this tradition, halal bihalal gatherings are not only social meetings but also carry deep religious and cultural values, reinforcing brotherhood and solidarity among community members. Although this concept is not explicitly mentioned in the Quran, the teachings of forgiveness and maintaining connections are significant principles in Islam, supported by various Quranic verses and hadiths. The history of this tradition dates back to the era of the Walisongo in the 15th century and later evolved through the efforts of religious figures and community leaders, including KH Wahab Chasbullah in 1948. In Java, halal bihalal is marked by the customs of sungkeman (a gesture of respect and apology) and communal meals, showcasing principles like ngaku lepat (admitting mistakes) and symbolism in food, such as ketupat, which represents acknowledgment of faults. Within Islamic and Javanese culture, halal bihalal is not merely about asking for forgiveness but also about fostering social and spiritual harmony within the community. Keywords: Halal Bihalal, Silaturahmi, Javanese Tradition. Abstrak Halal bihalal merupakan tradisi khas Indonesia yang dilakukan setelah bulan Ramadan, sebagai momen untuk saling memaafkan dan mempererat silaturahmi antarindividu maupun kelompok masyarakat. Istilah "halal bihalal" berasal dari bahasa Arab dan mengalami akulturasi dengan budaya Jawa. Dalam tradisi ini, acara halal bihalal tidak hanya menjadi pertemuan sosial tetapi juga mengandung nilai-nilai religius dan budaya yang mendalam, memperkuat persaudaraan dan solidaritas antaranggota masyarakat. Meskipun konsep ini tidak secara eksplisit disebutkan dalam Al-Qur'an, ajaran tentang memaafkan dan menyambung tali silaturahmi merupakan prinsip penting dalam Islam, didukung oleh berbagai ayat Al-Qur'an dan hadits. Sejarah tradisi ini ditemukan sejak era Walisongo di abad ke-15, yang kemudian berkembang melalui peran para tokoh agama dan pemimpin masyarakat, salah satunya oleh KH Wahab Chasbullah pada tahun 1948. Halal bihalal di Jawa diwarnai dengan adat sungkeman dan makan bersama, menampilkan prinsip ngaku lepat dan simbolisme dalam makanan seperti ketupat yang menandakan pengakuan atas kesalahan. Dalam tradisi Islam dan budaya Jawa, halal bihalal tidak hanya sebatas meminta maaf tetapi juga merawat harmoni sosial dan spiritual dalam komunitas. Kata kunci: Halal Bihalal, Silaturahmi, Tradisi Jawa.